ACCOUNTING AUTOMATION SYSTEMS IN ENTERPRISES (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
A clearly visible important aspect of the process of change in society is the global information system. Currently, under the influence of the general system of information exchange processes, an information society is being formed that is capable of using modern knowledge in all areas related to human activity.